Autonomic neuropathy in Rheumatoid Arthritis: Relationship with seropositivity of Rheumatoid factor and disease activity - Jahan, Kawser; Begum, Noorzahan; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2022)
Background: Autonomic neuropathy (AN) has been recognized as a strong predictor of sudden cardiac death in Rheumatoid Arthritis (RA). Autonomic neuropathy may be assessed by five cardiovascular reflex tests. Objective: To find out the prevalence and severity of AN in RA and also to assess the correlation of inflammatory markers, disease severity and serological factor, Rheumatoid factor (RF) with autonomic reflex test parameters. Method: This cross sectional study was conducted on sixty (60) female RA patients, age range 18-50 years enrolled from the Out- Patient Department of Rheumatology Wing, Department of Medicine, of Bangabandhu Sheikh Mujib Medical University (BSMMU). Age matched 30 apparently healthy females were control. Cardiac autonomic reactivity was assessed by five cardiovascular reflex tests as described by Ewing include heart rate response to standing, deep breathing, valsalva maneuver and blood pressure response to standing and sustained hand grip. Inflammatory activity in RA was assessed by serum rheumatoid factor (RF)level which was estimated by the latex agglutination test ,C-reactive protein(CRP) and ESR and marker of disease activity was assessed by Disease activity score(DAS- 28 score) value. For statistical analysis, independent sample ‘t’ test chi-square test, pearson correlation coefficient test, spearman correlation test were used. Results: Among 60 RA patients, 43 (71.6%) patients were RF positive. Frequency of AN in RA patients was significantly higher (p< 0.001) compared to control. AN was detected in 78% of RA patients. Among the RA patients 17.38% showed severe,13.04% showed definite, 54.35% showed early involvement and 17.38% showed evidence of atypical pattern of AN. In addition, valsalva ratio and difference between maximum and minimum heart rate during deep breathing showed significant(p<0.05) negative correlation with autoantibody Rheumatoid factor(RF) whereas no significant correlation of autonomic nerve reactivity parameters with DAS- 28, CRP and ESR were found. Conclusion: Autonomic neuropathy was associated with RA. Autonomic neuropathy may be related to the presence of autoantibody RF in RA patients. J Bngladesh Soc Physiol 2021;16(1): 70-76